Mild Gestational Diabetes and Adverse Pregnancy Outcome: A Systemic Review and Meta-Analysis - Bidhendi Yarandi, Razieh; Vaismoradi, Mojtaba; Panahi, Mohammad Hossein; Gåre Kymre, Ingjerd; Behboudi-Gandevani, Samira (Frontiers in Medicine, 2021)
Objectives: To investigate the impact of mild GDM on the risk of adverse maternal and neonatal outcomes. Methods: A systematic literature search was conducted to retrieve articles published in English that compared adverse maternal and neonatal outcomes among women with mild GDM in comparison with non-GDM counterparts. All populations were classified to three groups based on their diagnostic criteria for mild GDM. Results: Seventeen studies involving 11623 pregnant women with mild GDM and 53057 non-GDM counterparts were included. For adverse maternal outcomes, the women with mild GDM had a significantly higher risk of cesarean section (pooled RR: 1.3, 95% CI 1.2–1.5), pregnancy-induced hypertension (pooled RR: 1.4, 95% CI 1.1–1.7), preeclampsia (pooled RR: 1.3, 95% CI 1.1–1.5) and shoulder dystocia (pooled RR: 2.7, 95% CI 1.5–5.1) in comparison with the non-GDM population. For adverse neonatal outcomes, the pooled relative risk of macrosomia (pooled RR = 0.4, 95% CI: 1.1-1.7), large for gestational age (pooled RR = 1.7, 95% CI: 1.3-2.3), hypoglycemia (pooled RR = 1.6, 95% CI: 1.1-2.3), hyperbilirubinemia (pooled RR = 1.1, 95% CI: 1-1.3), 5 min Apgar less than 7 (pooled RR = 1.6, 95% CI: 1.1-2.4), admission to the neonatal intensive care unit (pooled RR = 1.5, 95% CI: 1.1-2.1), respiratory distress syndrome (pooled RR = 3.2, 95% CI: 1.8-5.5) and preterm birth (pooled RR = 1.4, 95% CI: 1.1-1.7) significantly increased in the mild GDM women compared with the non-GDM population. The adverse events of small for gestational age and neonatal death were not significantly different between the groups. Analysis of composite maternal and neonatal outcomes revealed that the risk of those adverse outcomes in the women with mild GDM in all classifications were significantly higher than the non-GDM population. In the meta-regression, the magnitude of those increased risks in both composite maternal and neonatal outcomes were similar. Conclusion: The risks of sever adverse neonatal outcomes including small for gestational age and neonatal mortality are not increased with mild GDM. However, the increased risks of most adverse maternal and neonatal outcomes are observed. The risks have similar magnitudes for all mild GDM diagnostic classifications.